2020
DOI: 10.5039/agraria.v15i1a6288
|View full text |Cite
|
Sign up to set email alerts
|

Growth and production of crisphead lettuce cultivars in protected cultivation and high temperatures

Abstract: and Delícia in four production environments covered with red, chromatinet ® , black shading nets, and under full sun, with the a randomized blocks design in a 4 x 8 factorial scheme. The harvest was at 45 days after transplanting and the following was determined: head formation index, leaf length and width, plant height, stem length, head diameter, total and commercial fresh matter, total and commercial yield. Data were subjected to analysis of variance, and means were compared by the Scott-Knott test at 5%. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
1
0
3
Order By: Relevance
“…Na primeira época, nota-se que o maior valor para massa fresca da parte aérea foi observado na cultivar Lucy Brown com média de 192,69 Segundo Souza et al (2013), no cultivo de alface americana é de se esperar comportamento morfológico variável quando submetida a diferentes condições edafoclimáticas. Isso porque fenômenos que ocorrem durante a fase de formação de cabeças podem envolver respostas do metabolismo das plantas relacionadas a temperaturas, fotoperíodo, umidade, nutrição, intensidade de luz e outros fatores que podem atuar individualmente ou em conjunto, conforme reporta Aires et al (2020), ao estudarem o efeito de ambientes favoráveis ao desenvolvimento da cultura de alface americana.…”
Section: Resultados E Discussõesunclassified
See 2 more Smart Citations
“…Na primeira época, nota-se que o maior valor para massa fresca da parte aérea foi observado na cultivar Lucy Brown com média de 192,69 Segundo Souza et al (2013), no cultivo de alface americana é de se esperar comportamento morfológico variável quando submetida a diferentes condições edafoclimáticas. Isso porque fenômenos que ocorrem durante a fase de formação de cabeças podem envolver respostas do metabolismo das plantas relacionadas a temperaturas, fotoperíodo, umidade, nutrição, intensidade de luz e outros fatores que podem atuar individualmente ou em conjunto, conforme reporta Aires et al (2020), ao estudarem o efeito de ambientes favoráveis ao desenvolvimento da cultura de alface americana.…”
Section: Resultados E Discussõesunclassified
“…Valor superior de massa fresca (559,3 g) foi encontrado por Yuri et al (2005) na cultivar Lucy Brown, quando cultivada no interior de túnel alto com mulching preto, no período de setembro a novembro, nas condições agroclimáticas de Santo Antônio do Amparo -MG. Santana et al (2009), na região do sub-médio São Francisco -BA, em condições semelhantes de cultivo sob canteiro convencional, tiveram rendimento de 304 e 351 g para as cultivares Grandes Lagos e Rafaela, valores superiores aos do presente estudo em condição climática favorável para alface americana, conforme apontado por Aires et al (2020).…”
Section: Resultados E Discussõesunclassified
See 1 more Smart Citation
“…Ethylene, a gaseous hormone, is used by plant roots to detect soil compaction (Huang et al, 2022). In a lettuce study, Aires et al (2020) reported that the ethylene response factor1 (LsERF1) transcription factor was absorbed under high-temperature stresses and assisted lettuce in germinating. LsERF1 is a transcription factor involved in the ET signaling pathway.…”
Section: Et As a Plant Growth Regulator On Various Stress Factorsmentioning
confidence: 99%